Alveolar Pco2 and Po2 of high-altitude natives living at sea level. - León-Velarde, F; Vargas, M; Monge-C, C; Torrance, R; Robbins, P (1996)
This study was designed to determine whether subjects born at high altitude (HA; 2,000 m or above) who subsequently move to near sea level (SL) develop end-tidal PCO2 (PETCO2) and PO2 (PETO2) values that equal those of SL natives living near SL. A total of 108 male HA natives living near SL were identified by survey of a district in Lima, Peru, and a further 108 male SL natives from the same district were identified as control subjects. Of these subjects, satisfactory data for inclusion in the study were obtained from 93 HA and 82 SL subjects. Mean PETCO2 and PETO2 values were 37.7 +/- 2.5 (SD) and 104.7 +/- 3.2 Torr, respectively, in HA subjects and 37.7 +/- 2.2 and 104.8 +/- 3.0 Torr, respectively, in SL subjects. The average difference between SL natives and HA natives for PETCO2 was 0.07 Torr (-0.64 to 0.78; 95% confidence interval) and for PETO2 was 0.05 Torr (-0.89 to 0.99, 95% confidence interval). The average age and weight of the SL and HA subjects did not differ, but the HA subjects were shorter and tended to have larger vital capacities, consistent with their origin at HA. We conclude that the PETCO2 and PETO2 near SL of SL natives and HA natives do not differ.